2004
DOI: 10.1088/0031-9155/49/5/004
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of EEG and MEG measurements to tissue conductivity

Abstract: Monitoring the electrical activity inside the human brain using electrical and magnetic field measurements requires a mathematical head model. Using this model the potential distribution in the head and magnetic fields outside the head are computed for a given source distribution. This is called the forward problem of the electro-magnetic source imaging. Accurate representation of the source distribution requires a realistic geometry and an accurate conductivity model. Deviation from the actual head is one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
88
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 30 publications
7
88
0
Order By: Relevance
“…There is a broad consensus that forward model uncertainty is an important limiting factor for EEG imaging by source reconstruction [17,24,55,56,57,58,59]. Our results add quantitative evidence to this view, both in terms of the tissue conductivity ratio, which is the main source of uncertainty if the brain topography is correct, and more broadly when both anatomy and conductivities are unknown.…”
Section: Discussionsupporting
confidence: 65%
“…There is a broad consensus that forward model uncertainty is an important limiting factor for EEG imaging by source reconstruction [17,24,55,56,57,58,59]. Our results add quantitative evidence to this view, both in terms of the tissue conductivity ratio, which is the main source of uncertainty if the brain topography is correct, and more broadly when both anatomy and conductivities are unknown.…”
Section: Discussionsupporting
confidence: 65%
“…For the class of superficial neocortical sources, we chose two dipoles in the right somatosensory cortex, one of them approximately tangentially oriented (in the posterior -anterior direction) and the other approximately radially oriented (in the inferior -superior direction). Because it is known that both EEG and MEG are especially sensitive to conductivity changes in the vicinity of the dipole (Haueisen et al, 2000;Gencer and Acar, 2004), we checked the environment of the superficial somatosensory sources and found that only 15% of the surrounding finite elements were labeled as white matter and 0% as skull. The representative of the second class, deep sources, was chosen in the left thalamus, where the source orientation is approximately radial.…”
Section: Simulated Sourcesmentioning
confidence: 99%
“…One impediment to using the FE method -and to this type of modeling in general -has been the high computational cost of carrying out the simulations. The use of recently developed advances in the FE method in EEG/MEG inverse problems (Weinstein et al, 2000;Wolters et al, 2002;Gencer and Acar, 2004;Wolters et al, 2004b) dramatically reduces the complexity of the computations, so that the main disadvantage of FE modeling no longer exists. In realistic FE models, sensitivity studies have been carried out for the influence of skull anisotropy on EEG and MEG (van den Broek et al, 1998;Marin et al, 1998;Wolters, 2003), while, to our knowledge, only a few studies have investigated the influence of realistic white matter anisotropy Wolters, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the source localization techniques use a default value for this parameter. However, this value can affect the reconstruction considerably [3], [6]- [8] and has been shown to vary significantly across different subjects [2], [9]. To increase the reconstruction quality without measuring the skull conductivity directly, several methods try to estimate it jointly with the brain activity directly from the M/EEG measurements [10]- [17].…”
Section: Introductionmentioning
confidence: 99%